Electrochemical sensor based on 1,8-dihydroxyanthraquinone adsorbed on a glassy carbon electrode for the detection of [Cu(CN)3](aq)2− in alkaline cyanide copper plating baths waste - Cardenas-Riojas, Andy A. (2021)
This work reports the fabrication of a novel electrochemical sensor for the detection of the complex ion [Cu(CN)3](aq)2−, one of the main components of the effluents from cyanide alkaline copper plating baths. This sensor was prepared by using a surface modified glassy carbon (GC) electrode with 1,8-dihydroxyantroquinone (1,8-DHAQ). It was characterized by electrochemical impedance, Raman spectroscopy and UV–Visible spectroscopy. The electrochemical detection of [Cu(CN)3](aq)2−was performed by differential pulse voltammetry. The 1,8-DHAQ/GC electrochemical sensor exhibits good reproducibility and a linear range of 5.50 × 10−7–3.81 × 10−6 mol L−1, with a detection limit (LOD) of 1.20 × 10−6 mol L−1, quantification limit (LOQ) of 3.97 × 10−6 mol L−1, and robustness to interfering Cl−, NO3−, SO42− y CO32− ions. Finally, a DFT approach suggests an almost parallel orientation of the bis(1,8-dihydroxyanthraquinone) over a graphene domain of the glassy carbon surface, as well as the noncovalent nature of the interactions involved. © 2020